Exploring the repellent and insecticidal effects of black Pepper (Piper nigrum L.) against sawtoothed grain beetle (Oryzaephilus surinamensis L.) - Nurul Farah ‘Aina Anuar,; Nurul Huda Abdul, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Oryzaephilus surinamensis, also known as the sawtoothed grain beetle, is a widely distributed storage pest that thrives in products with high sugar and carbohydrate contents. Every year, O. surinamensis causes devastating losses in post-harvest and stored products, particularly grain products. The aim of this study was to determined the repellence and toxicity actions of black pepper (Piper nigrum) against O. surinamensis. The repellence bioassay was conducted using two types of treatments, hot infusion of black pepper powder at concentrations of 25, 50, 75 and 100 g/L and commercial black pepper oil at 1.25, 2.50, 3.75, and 5.00 mL/L. A toxicity bioassay through contact was also investigated using commercial black pepper oil at the same concentrations. The highest repellence action was recorded at 25 g/L (5.70±1.055) for hot infusion and at 2.50 mL/L (5.40±0.400) for commercial black pepper oil. Meanwhile, in the toxicity bioassay, mortality was recorded to reach 50% after 6 hours and 24 hours of exposure at 3.75 mL/L and 2.50 mL/L concentrations, respectively. The highest mortality was recorded at 3.75 mL/L (20.75±1.315) and reached 83% after 48 hours of exposure. Thus, it can be said that black pepper, despite being prepared in the simplest way possible for use in the home, is a potent insect deterrent and excellent biopesticide against the sawtoothed grain beetle.